PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN TUPPERWARE (Studi Kasus Pada PT. WIDYA MUTIRA BALI di Denpasar) - Ni Made Wulan Pradnyadewi; Dewiwati Sujadi (Universitas Triatma Mulya, 2020)
This study aims to analyse the effect of product quality and price on purchasing decisions Tupperware. The number of samples in this study were 119 respondents. Data collection techniques in this study are questionnaires, documents and interviews. Sampling uses the purposive sampling method, which is a sampling technique that is carried out for certain purposes and considerations. The research method used in this research is quantitative descriptive method. While the method of data analysis using multiple linear regression with T-test. Partially product quality (X1) and price (X2) have a positive and significant effect on purchasing decisions (Y) at PT.Widya Mutiara Bali. product quality (X1) and price (X2) have a positive and significant effect on purchasing decisions (Y) at PT.Widya Mutiara Bali. Based on the results of the study obtained a regression equation model Y=10,250+0,214X1+0,184X2, meaning that if there is an increase in product quality then the purchasing decision at PT. Widya Mutiara Bali will increase by 0.214 and if there is an increase in prices, the purschasing decision at PT. Widya Mutiara Bali will increase by 0.184. This means that there is a positive and significant influence between product quality and price on Tupperware purchasing decisions at PT. Widya Mutiara Bali. Implications for companies are to always improve product quality and maintain prices so that purchasing decisions can be maintained.